LEGAL PROTECTION OF UNDERAGE WORKERS FROM THE VIEWPOINT OF CHILDREN'S RIGHTS IN INDONESIA - Hanifah, Ida (Proceeding International Seminar of Islamic Studies, 2024)
Described in Law Number 13 of 2003 concerning Employment of minors is explained in Article 1 paragraph 26 "A child is every person under the age of 18 (eighteen) years". Meanwhile, according to Article 1 number 2 of Law Number 13 of 2003 concerning Manpower, manpower is anyone who is able to do work to produce goods/services both to meet their own needs and for the community, while workers/laborers according to Article 1 point 3 of the Law Number 13 of 2003 concerning Manpower states that a worker or laborer is anyone who works and receives wages or other forms of compensation. 13 Law Number 13 of 2003 focuses on the protection of children who are bound by a work relationship as stated in article 68 "Entrepreneurs are prohibited from employing Child". However, in Article 69 there is an exception as contained in paragraph (1). The provision as stated in Article 68 can exclude children between the ages of 13 (thirteen) to 15 (fifteen) years from doing light work as long as it does not interfere with their development and health. physical, mental, and social. However, in paragraph (2) it is explained that employers may employ the following: "Entrepreneurs who employ children in light work as referred to in paragraph (1) must meet the requirements. This Labor Law also concerns protection. the law on wages, as well as regarding the welfare of child labor contained in CHAPTER X there are provisions in Article 68 to Article 75 in this chapter. Where in Article 68 it stipulates that employers may not employ children. Philosophically, the sole purpose of the prohibition on employing children is for the sake of these children receiving legal protection for the growth and development of the child itself, also in the development of his dignity to prepare the child's future.